Cutaneous infectionbydifferent Alternaria species inalivertransplant recipient - Brás, S. (2015)
Fungal invasive infections are rare in general population but are an emergent cause of infection in the immunocompromized population, especially in the solid organ transplant recipients. Herein the authors report a clinical case of a liver transplanted patient suffering a cutaneous co-existent infection with A. alternata as well as A. infectoria. To our knowledge this is the first case of cutaneous concomitant infection due to those two species reported not only in Portugal but also worldwide. The patient was treated with surgical excision of the lesions and oral itraconazol without relapse.